PENGEMBANGAN E-MODUL INSTALASI PENERANGAN LISTRIK BERBASIS PROJECT BASED LEARNING DI SMK - Siregar, Winda Lestari; Usmeldy, Usmeldy (Patria Artha Technological Journal, 2021)
The purpose of this research is to produce a valid, practical, and effective e-modules for Project Based Learning in Electrical Lighting Installation. This e-modules of the Project Based Learning in Electrical Lighting Installation module is designed to improve students' understanding that it can improve student learning outcomes. The method in this study uses Research and Development (RD) with 4-D development procedures (Define, Design, Develop, Desseminate).The data of analysis technique uses descriptive analysis techniques to describe the validity, practicality, and effectiveness of the e-modules for Project Based Learning in Electrical Lighting Installation. The results obtained from this development research: The validity of the e-modules for Project Based Learning in Electrical Lighting Installation is declared valid on the media and material aspects.The practicality of the e-modules for Project Based Learning in Electrical Lighting Installation from the teachers and students respones is stated to be very practical. The effectiveness of the e-modules for Project Based Learning in Electrical Lighting Installation is stated to be effective in improve to learn the outcomes. Based on the findings of this study, it is concluded that the e-modules of Project Based Learning in Electrical Lighting Installation is valid, practical, and effective to be used as a learning aid.